Can you show steps please? Thanks!
5 Answers

Factor: x^3 – 3x^2 – 10
Answer:
x(x^2 – 3x – 10) = 0
x[(x^2 – 3x + 9/4) – 10 – 9/4] = 0
x[(x – 3/2)^2 – 49/4] = 0
I like to always use completing the square for all quadratics
first x:
x = 0
second x:
[(x – 3/2)^2 – 49/4] = 0
(x – 3/2)^2 – 49/4 = 0
(x – 3/2)^2 = 49/4
x – 3/2 = +/ sqrt (49/4)
x = 3/2 +/ sqrt (49/4)
x = 3/2 +/ 7/2
x = 5 or x = 2
So all your x as factors: (x)(x5)(x+2)

1.) Notice that an x appears in every term. You can factor out this x to make the new form:
x(x^23x10)
2.) Now factor the section inside the parenthesis:
x(x5)(x+2) <— You do this by noticing that 5 and 2 multiply to make 10 and add to make 3.

x^(3)3x^(2)10x
Factor out the GCF of x from each term in the polynomial.
x(x^(2))+x(3x)+x(10)
Factor out the GCF of x from x^(3)3x^(2)10x.
x(x^(2)3x10)
For a polynomial of the form x^(2)+bx+c, find two factors of c (10) that add up to b (3). In this problem 2*5=10 and 25=3, so insert 2 as the right hand term of one factor and 5 as the righthand term of the other factor.
x(x+2)(x5)

Its actually quite simple, all you do is factor out the x so the equation would be x(X^23x10), solve the inside as you normally would with a quadratic and then multiply x to the answers.
Work:
x(x^23x10)
x((x5)(x+2))
Source(s): Algebra 2 Trigonometry as a Sophomore in High School 
x^3 – 3x^2 – 10x
x (x^2 – 3x – 10)
x (x – 5)(x + 2)